Accountability of management of school operational funds in Madrasah Tsanawiyah (MTs) in Purbalingga District - Wirawan, Didik; Hayu Dwimawanti, Ida; Indarti, Sri (Trigin Publisher, 2023)
There were issues with the way BOS funding were being handled by MTs in the Purbalingga District. The goal of this research was to identify who was responsible for overseeing Madrasah Tsanawiyah (MT) accounts in Purbalingga Regency's School Operational Assistance (BOS) program. The interviews used in this study are the primary data in a qualitative research study. Five MTSs within the Purbalingga Ministry of Religion who had received BOS funding were interviewed. According to the findings, five MTs in the Purbalingga District have developed a strategy for estimating the school's annual revenue and costs. According to article 53 of PP NO 19 of 2005, which establishes minimum requirements for public schools, this institution has taken the necessary steps to implement them. The school relies on technical requirements for the administration of BOS to ensure that all data is accurate and full. Schools have successfully adapted to the intended use of BOS money in accordance with established technical criteria. It follows the rules laid out by the BOS's technical standards for the administration of normal BOS funds, guaranteeing its legitimacy and uniformity. The BOS fund manager has also generated a report of accountability in line with the rules. Challenges to transparency in the use of BOS money in five Purbalingga Municipalitiesa lack of community involvement in monitoring the administration of BOS funds in schools, and the difficulty of generating reports on the use of BOS funds due to the volume of work required of the BOS treasurer.